Instalación y Operación de Sistemas PACS (Almacenamiento y Comunicación de Imágenes): Características Fundamentales - Azpiroz Leehan, J.; Martínez Martínez, M. (Revista Mexicana de Ingenieria Biomedica, 1998)
Visual analysis of medical images is a fundamental tool of clinical diagnosis. Today, 80% of medical images are printed on radiographic film without regard to their origin, even when the original image is digital and the printing process degrades the image quality. The development of digital tomography and other numerical methodologies have produced different types of data formats and digital storage systems. In the 80’s emerged the idea of creating a 100% digital radiology and imaging department. Such a department would rely on a network of image workstations, digital storage systems, and the image acquisition devices. This complete system has been named PACS (Picture Archiving and Communication System). This article presents a review of the fundamental characteristics of such systems and the applicable standards.